Effectiveness of Toileting Training Mediated With Animated Videos Against To Independence Level of Toileting on Pre-School Children - Ernawati, Nunung; Permata, Kartika (Journal Of Nursing Practice, 2019)
Background:The one of development tasks for preschooler that must be passed is toileting activity. Toileting learning need should start at toodler phase, but many children still enuresis experience in the classroom, all students could not do proper toileting, including not knowing how to go to the toilet, not being able to open the pants and not being able to flush the elimination urine and defecatie in Kindergarden-class A of Malang City. Inability to control of elimination urine that cause of pre schooler are less independece for toileting activity.Purpose: to find out the effect of toilet training mediated with animated videos againts to independence level of toileting on pre schooler children in kindergarten-class A of Malang City.Methods: This type of research was analytic observation with a pre-experimental approach. The total population was 38 children, the number of samples 38 children was taken using the total sampling technique. The variable measured is the level of independence of toileting. The data was processed then analyzed using the Wilcoxon test with ? <0.05.Results: Based on the results of the study, the level of independence before toileting learning was done 21% independently and 79% not independently. The level of independence after toileting learning is 100% done independently.Wilcoxon test was analyzed, the level of independence was obtained with a p-value of 0,000 which means that p-value <? so that H0 is rejected, which means there is an influence of the learning activity of animated videos on the level of independence of toileting.Conclusion:Based on the results of the study, to improve children's independence, in terms of toileting, can be done early and in the future learning, animated video media can be used as an alternative as a learning media for pre-schooler.